Effectiveness Of Summarizing Strategy In Developing Reading Comprehension Among Tenth Graders At SMA Negeri 5 Palu - Fajria Dolita; Darmawan Darmawan; Hastini Hastini; Abdul Kamaruddin (ELS Journal on Interdisciplinary Studies in Humanities, 2025)
The aim of this study was to find out the effect of the summarizing strategy on improving students’ reading comprehension at SMA Negeri 5 Palu. This research was based on an initial study that showed many students still struggled to understand texts, had difficulty finding main ideas and detailed information, and lacked vocabulary. The researcher used the summarizing strategy as a method to help improve students’ reading skills. This study used a quasi-experimental design. The population was tenth-grade students at SMA Negeri 5 Palu, involving classes X M5 and X M3, with 35 and 32 students respectively. To collect the data, the researcher used pre-tests and post-tests to measure students’ abilities before and after the treatment. The results of data analysis showed a significant improvement in reading comprehension. The average score of the experimental group increased from 68.85 to 79.06, while the average score of the control group slightly decreased from 69.33 to 67.52. Data analysis showed a significance value (2-tailed) of 0.000 < 0.050, which means that Ha was accepted. It can be concluded that the summarizing strategy significantly improved students’ reading comprehension.